Comparative Implementation of the Free Nutritious Meal Program in Public and Private Schools as a Form of Social Justice - Andi Meiky Al Paris; Citra Abriyanti Octavia Sitorus; Oksep Adhayanto (Ekasakti Journal of Law and Justice, 2026)
This study aims to analyze the implementation of the Free Nutritious Meal Program (Program Makan Bergizi Gratis/MBG) in Indonesia through the lens of social justice, with a comparative focus between public and private schools. Employing a normative juridical research method with a qualitative descriptive approach, the findings reveal that the current MBG distribution pattern remains universal and institution-based, without differentiating students' economic conditions. This results in an imbalance of effectiveness: the program is considered highly targeted and produces significant impact in public schools, which serve students from diverse socioeconomic backgrounds, yet risks being poorly targeted and generating budgetary waste in private schools predominantly attended by students from affluent families. The study concludes that although an equality-based approach has been achieved, the substantive social justice principle of equity has not been fully realized. Consequently, policy evaluation is needed to shift the distribution of assistance toward a need-based approach, ensuring more effective, efficient, and purposeful resource allocation for vulnerable groups.